2005
DOI: 10.2174/1566523054546189
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptionally Targeted Adenovirus Vectors

Abstract: Adenovirus vectors are the most highly efficient vehicles currently available for gene transfer to mammalian cells. Their ability to transduce both proliferating and non-dividing cells allows in vivo gene delivery, but the wide spectrum of cell types infected by adenovirus necessitates a requirement for targeting, particularly if the transduced gene is detrimental when expressed in inappropriate tissues. Over the past decade, numerous investigators have examined tissue- or tumor-specific enhancer-promoters as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 140 publications
(172 reference statements)
0
43
0
Order By: Relevance
“…In earlier studies, rAAV2-R484E;R585E showed strongly reduced transduction of mouse hepatic tissue in vivo, with slight increase in heart transduction. 26,38 Thus, this experiment should clarify whether the ablation of heparin binding alone-which may result from insertion of a peptide at position R588-would result in similarly increased heart targeting (Figures 3b [4] and [5] and c [4] and [5]). Mutation of the heparin-binding motifs indeed slightly increased heart infection and dramatically reduced liver transduction.…”
Section: Aav Targeting Y Ying Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…In earlier studies, rAAV2-R484E;R585E showed strongly reduced transduction of mouse hepatic tissue in vivo, with slight increase in heart transduction. 26,38 Thus, this experiment should clarify whether the ablation of heparin binding alone-which may result from insertion of a peptide at position R588-would result in similarly increased heart targeting (Figures 3b [4] and [5] and c [4] and [5]). Mutation of the heparin-binding motifs indeed slightly increased heart infection and dramatically reduced liver transduction.…”
Section: Aav Targeting Y Ying Et Almentioning
confidence: 99%
“…Mutation of the heparin-binding motifs indeed slightly increased heart infection and dramatically reduced liver transduction. However, a broad distribution in other organs and a significant accumulation in the skeletal [4] and [5] and c [4] and [5]), clearly indicating a positive targeting effect of the two selected peptides.…”
Section: Aav Targeting Y Ying Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, human adenovirus (Ad) has been widely used as a vector for gene transfer to mammalian cells, owing to its ability to effectively infect a wide variety of cells [20]. Replication deficient viruses proliferate for weeks in hosts with cancer or other diseases, enabling the restored expression of a defected gene to achieve therapeutic goals.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches have been made to transcriptionally regulate the expression of therapeutic genes in cancer cells reviewed in references. [2][3][4][5][6][7][8][9][10][11][12] However, interference from the adenoviral sequences can significantly alter the transcriptional control. [13][14][15][16][17] One proven method to block interference of the adenoviral sequences with tissue-specific or -inducible promoters is to include the chicken b-globin HS4 insulator element.…”
Section: Introductionmentioning
confidence: 99%